The place of Ireland in the development of American global thought in the later nineteenth and early twentieth centuries - Martin, Kyle (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2021)
This thesis is a study of a particular dimension of American political and historical thought in the late nineteenth and early twentieth centuries. During this period American writers and intellectuals acknowledged, promoted, and defended the arrival of the United States as an economic and political power in comparison to other world powers. Central to this self-perception was an awareness that conventional American perceptions of the character and aims of the supreme global power, Great Britain, demanded examination and reassessment. Essential to those subsequent perceptions was a need to address the most troublesome and problematic region in the British Isles, Ireland. This thesis investigates the manner in which this particular vein of thought was developed and found expression in the main organs of American public opinion and academic discourse. The American writers and intellectuals who participated in this debate argued over visions of an imperial United States as the counterpoint to the British Empire. This study documents and analyzes the substance of their accounts of Irish history and politics, which they used to define the difference of American global thought from the British example. Within their assessment of Ireland, they revealed an ambiguous attitude about the rise of the United States in the world.
APPROVED
Keywords: American global thought; imperialism; empire; American imperialism; Irish America; Anglo-American relations; British Empire